2022
DOI: 10.3390/w14081194
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Contamination along the Tigris River from Tharthar-Tigris Canal to Azizziyah, Middle of Iraq

Abstract: The Tigris River is the second-longest river in Western Asia and runs through heavily populated areas, especially in Baghdad city with nearly 8 million inhabitants. The water demand is at its highest levels, nevertheless the Tigris discharge has severely declined in the last decades; combined with the fact that the wastewater quantities are increasing, and the wastewater treatment plants are experiencing a deficiency. Four sites were chosen: the Tharthar-Tigris Canal which is located in the north part of Baghd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Only PI for Zn has no effect on all sites and for both seasons. While most of the elements have PI values of less than 1, except for Pb, where values are larger than 1 in all sites in both seasons and always fall under the "Seriously Affected" class, which may be due to anthropogenic metals loaded from industrial activity, where the studied area is characterized by the presence of industrial complex plants [20]. In a study by Parissa et al, 2012 [21], it was reported that one of the well-known sources of Pb in water is the deposition of this element from the atmospheric layer to water from vehicular traffic.…”
Section: Resultsmentioning
confidence: 94%
“…Only PI for Zn has no effect on all sites and for both seasons. While most of the elements have PI values of less than 1, except for Pb, where values are larger than 1 in all sites in both seasons and always fall under the "Seriously Affected" class, which may be due to anthropogenic metals loaded from industrial activity, where the studied area is characterized by the presence of industrial complex plants [20]. In a study by Parissa et al, 2012 [21], it was reported that one of the well-known sources of Pb in water is the deposition of this element from the atmospheric layer to water from vehicular traffic.…”
Section: Resultsmentioning
confidence: 94%
“…In general, all the studied symptoms, despite the presence of a relative height for most of them, were within the permissible limits for drinking, with the appearance of some fecal coliform bacteria cells in some periods. It is noted from Table (4) that the temperatures rise in some periods to reach (20) ˚C, which stimulates the activity of bacteria when present in the water (Oleiwi and Al-Dabbas, 2022).…”
Section: Excelmentioning
confidence: 99%
“…The source of these trace elements may be from anthropogenic inputs into soils from different sources, such as agricultural fertilizers, atmospheric deposition, traffic emission, and sewage sludge (Oleiwi and Al-Dabbas ,2022). In general, it is believed that the analyzed trace elements are controlled by parent or source rocks, climatic conditions, pyogenic processes, and drainage where the soils and surface sediments of Mesopotamia terrains are immature with little modifications or alterations by pyogenesis and have undergone degradation by fluvial processes.…”
Section: Trace Elementsmentioning
confidence: 99%
“…Salinization of the upper part of the Mesopotamia sediments is induced by poor drainage, little rainfall, and very high evaporation rates. The Major ions and trace elements concentration in the surface water appear to have been mainly influenced by the type of source rocks of the Tigris River and its tributaries (Oleiwi and Al-Dabbas ,2022).…”
Section: Trace Elementsmentioning
confidence: 99%